Event Management Strategy of Darussalam Gontor Modern Islamic Boarding School In Organizing Panggung Gembira 2017 - fajar muarif muarif; Abdullah Abdullah (Universitas Darussalam Gontor, 2018)
Abstract The success of a performing arts event by Event Management is determined by the strategy implemented by Event Management itself. A good strategy in management is to implement four management functions; planning, organizing, actuating and controlling so that the activities has run systematically, professionally, effectively and efficiently.The purpose of this study are to explain and to describe how the strategy of Event Management Darussalam Gontor Islamic Boarding School especially when viewed from the planning, organizing, mobilization and supervision in organizing the art performance that is, Panggung Gembira. This research can also be a reference to art performances organized by various institutions, especially the education of Islamic Boarding School. The method used in this research is a qualitative descriptive. The Data were collected through observation, interview and documentation. While, data analysis where taken from data reduction, data presentation and taking conclusion. At this stage, Event Management Darussalam Gontor Islamic Boarding School could run systematically, professionally effective and efficient by applying the four management functions. In the planning function, determined goals and set implementation steps. In the second stage of organizing, assigning work and dividing the work to every member of the organization. The third stage is the actuating or movement. Mover is a leader who must have leadership and ability to communicate well to be able to run activities well. Stages of control are used to identify job standards, measure or assess work and take remedial actions in Panggung Gembira.Keyword: Strategy, Event Management, Panggung Gembira